Impact of teacher behaviour on the classroom engagement of normal stream students - Chong, Elizabeth. (2008)
This study was aimed at investigating the role of teacher behaviour in the classroom, with regard to the provision of classroom structure and teacher involvement in terms of engaging the students in classroom learning, how engagement is related to streaming and one's level of motivation and whether these two factors influence each other in determining the degree of engagement.